The Electronic Portfolio as Assessment Tool and More: The Drake University Model - Cadd, Marc (IALLT Journal of Language Learning Technologies, 2012)
The utilization of portfolios has become more common in academia in the last two decades. However, their usage in the language classroom is still relatively rare. Electronic portfolios (ePortfolios) offer students and instructors numerous advantages over traditional means of assessment, including a means by which progress can be tracked longitudinally. These collections of artifacts can be used to demonstrate proficiency to prospective employers and graduate schools. The author provides one model that incorporates and utilizes current technologies as a basis for student-compiled electronic portfolios. In this model, students provide evidence of having met the linguistic and cultural objectives for each language course they take. Much of this evidence comes from in-depth, self-reflective writing, in addition to a number of artifacts selected by the students with direction from instructors. Detailed assessment rubrics are provided for evaluating both the electronic portfolio and the assignments that usually serve as the bases for the ePortfolio’s artifacts. This comprehensive model represents one alternative to assessment through “seat-time” or number of credit hours earned in a given language.